2018
DOI: 10.1111/jfpp.13773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium caseinate concentration and sonication amplitude on the stability and physical characteristics of homogenized coconut milk

Abstract: The ultrasonic homogenization of coconut milk with added sodium caseinate (SC) was carried out to reduce the fat globules size and stabilize the emulsion. The coconut milk was mixed with SC at different concentrations from 0.5% to 2% w/w. The sonication was conducted at different sonication amplitudes (60%, 80% and 100%). The primary and effective droplet size, viscosity, homogenization efficiency and free fat content of the homogenized emulsion were characterized. Ultrasonic homogenization significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Many types of packaging could be applied, such as carton systems (the most common, e.g., Tetra Pak), plastics, and glass. It could also be processed into reconstituted powder form using spray drying or drum drying [45].…”
Section: Processing Steps Of Plant-based Milkmentioning
confidence: 99%
“…Many types of packaging could be applied, such as carton systems (the most common, e.g., Tetra Pak), plastics, and glass. It could also be processed into reconstituted powder form using spray drying or drum drying [45].…”
Section: Processing Steps Of Plant-based Milkmentioning
confidence: 99%
“…US, through cavitation forces, brings about the breakdown of fat droplets increasing the stability of the emulsion. Accordingly, studies have reported the applications of ultrasound for preventing phase separation and increasing the stability of coconut milk (Abdullah et al, 2018). On the other hand, MW and OH resulted in increased droplet size of the emulsion and wider size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…These differences reflectance pattern for different kind of milk is caused by different treatment for each UHT procedure. The UHT procedure for cow milk causes loss at some contents [11], while UHT technique for soy and coconut milk requires some content addition so that it causes some contents percentage also increased [12], [13].…”
Section: Milk Spectral Resultsmentioning
confidence: 99%